Endoscopic mucosal resection (EMR) versus endoscopic submucosal dissection (ESD) for resection of large distal non-pedunculated colorectal adenomas (MATILDA-trial): rationale and design of a multicenter randomized clinical trial. Issue 1 (December 2016) - Backes, Y.; Moons, L.; van Bergeijk, J.; Berk, L.; ter Borg, F.; ter Borg, P.; Elias, S.; Geesing, J.; Groen, J.; Hadithi, M.; Hardwick, J.; Kerkhof, M.; et al.
Abstract Background Endoscopic mucosal resection (EMR) is currently the most used technique for resection of large distal colorectal polyps. However, in large lesions EMR can often only be performed in a piecemeal fashion resulting in relatively low radical (R0)-resection rates and high recurrence rates. Endoscopic submucosal dissection (ESD) is a newer procedure that is more difficult resulting in a longer procedural time, but is promising due to the high en-bloc resection rates and the very low recurrence rates. We aim to evaluate the (cost-)effectiveness of ESD against EMR on both short (i.e. 6 months) and long-term (i.e. 36 months). We hypothesize that in the short-run ESD is more time consuming resulting in higher healthcare costs, but is (cost-) effective on the long-term due to lower patients burden, a higher number of R0-resections and lower recurrence rates with less need for repeated procedures. Methods This is a multicenter randomized clinical trial in patients with a non-pedunculated polyp larger than 20 mm in the rectum, sigmoid, or descending colon suspected to be an adenoma by means of endoscopic assessment. Primary endpoint is recurrence rate at follow-up colonoscopy at 6 months. Secondary endpoints are R0-resection rate, perceived burden and quality of life, healthcare resources utilization and costs, surgical referral rate, complication rate and recurrence rate at 36 months. Quality-adjusted-life-year (QALY) will be estimated taking an area under the curve approach and using EQ-5D-indexes. Healthcare costs will be calculated by multiplying used healthcare services with unit prices. The cost-effectiveness of ESD against EMR will be expressed as incremental cost-effectiveness ratios (ICER) showing additional costs per recurrence free patient and as ICER showing additional costs per QALY. Discussion If this trial confirms ESD to be favorable on the long-term, the burden of extra colonoscopies and repeated procedures can be prevented for future patients. Trial registration NCT02657044 (Clinicaltrials.gov), registered January 8, 2016.